Applications of Bacteriocin and Protective Cultures in Dairy Products: A Mini-Review - Volpane, Van Vincent A.; Vergoza, Dand Mark M.; Alderite, Khaila L.; Bilang, Jean Stephanie D.; Villa, Nira Mae P. De; Domingo, Bryan M.; Foronda, Pamela T.; Lirio, Mary Rose F. (Asian Journal of Biological and Life Sciences)
The spoilage of food by microorganism is one of the novel topics being tackled today despite the wide range of preservatives present today. Antimicrobial metabolites may have the potential to inhibit the growth of pathogenic bacteria and have been increasing in research due to the rise of human health risk posed by harmful preservatives and the rise of eating raw foods. Bacteriocin is a considerable interest in the field of preservation, is produced by Lactic acid bacteria and considered to be a safe alternative to conventional antimicrobials. Additionally, Lactic acid bacteria naturally occur in dairy products. A number of applications of Bacteriocins have been reported to successfully control and inhibit pathogens in milk, yogurt, cheeses and other dairy products. Bacteriocin poses no threat to human health, supported by research indicating that Lactic acid bacteria are easily degraded by enzymes in the mammalian gastrointestinal tract. Overall, this can be an alternative to satisfy the increasing consumers’ demands for safe, fresh-tasting, dairy products. This review will focus on bacteriocin’s recent application, advantages and disadvantages.
Keywords: Bacteriocin; Dairy products; Protective culture